People of the screen how evangelicals created the digital Bible and how it shapes their reading of scripture - Dyer, John 1972- (New York, NY Oxford University Press, 2023)
'People of the Screen' traces the history of Bible software app development, showing the unique and powerful role evangelical entrepreneurs and coders have played in shaping its functionality and how their choices in turn shape the reading habits of millions of people around the world.
Also issued in print: 2023. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on November 23, 2022)
Keywords: Bible -- Criticism, interpretation, etc -- Data processing; Bible -- Reading; Bible and technology; Evangelicalism; Religion; Religion & beliefs